Introducing the Benefits of Learning TOEFL at Twelfth Grade of SMA Teladan Pematang Siantar: A Socialization - Simanjuntak, Ramindo Rini Sari; Simanjuntak, Maretha Diona; Hutagalung, Christina; Pandiangan, Gian Reynaldo; Turnip, Irma Wardani; Herman, Herman; Sihombing, Sabar Dumayanti; Munthe, Bangun (Indra Institute Research & Publication, 2023)
This study aims to conduct socialization regarding the introduction and benefits of TOEFL to grade XII students at Teladan High School in Pematang Siantar. This service activity was held a day on December 14, 2023. The implementation was carried out by the lecture and training method. Lectures and training in the form of material delivery on TOEFL and its benefits in the world of education. This research was conducted at Teladan High School Pematang Siantar involving 38 students of class XII MIPA 4. This socialization implementation consisted of three sessions, namely giving pre-test questionnaires about the TOEFL test, lecture sessions or explanations of socialization materials about the TOEFL test, and discussion sessions and giving post-tests to test students' understanding of socialization materials. The results of this socialization activity showed that students who participated in the initial socialization were not familiar with TOEFL and had never heard of it before. However, after gaining knowledge about TOEFL through socialization, their understanding increased and they were very enthusiastic. Post-test results showed a significant improvement until 30% in student scores if compared to pre-test